L'image d'Alexandre le Grand chez Trogue Pompée / Justin. Analyse de la composition historique des Histoires philippiques (livres 11 et 12) - Horn, Nelson (PrimaLun@, 2021)
The Historiae philippicae by Iustinus are a quite difficult work because they are actually written by two authors: in the first century BC, Trogus, a Gallic historian, wrote a now lost universal history; several centuries later, Iustinus wrote an epitome from his text, the one we know now. Books 11 and 12 of these Historiae deal with the life of Alexander the Great, from 336 when he became king, up to his death in 323. As far back as Antiquity, Alexander's conquest has been a very well documented subject and we are able to compare them to other Alexander's Histories. This is why we can now draw some precious conclusions about the manner the two authors wrote their works. Trogus seems to have used several hellenistic sources, following the frame of Cleitarchos from Alexandria who presented Alexander in a very favorable way. However, thanks to other sources, Trogus eroded this image and composed his text in order to show a dark portrait of the king that Iustinus faithfully preserved : Alexander indeed appears like a decadent man. Misleaded by oriental wealth and luxuries he degenerates from his Greek culture and his noble nature to become a Persian and a tyrant. Trogus contemporary readers may have recognized behind Alexander the image of Caesar and above all Antonius : that way they were condemned by the Gallic historian who was favorable to the peace and the moral values that the new Augustus intended to champion.